(untitled) (Journal of Environmental Science and Natural Resources, 2015)
In Bangladesh, agriculture play an important role in sector of the economy and it is highly dependent on climate. The present study was conducted to assess farmers perception on climate change and soil carbon sequestration (SCS) in the Ludhua village under Senbagh upazilla of Noakhali district during November 2012 to February 2013. The study consisted of 94 randomly selected farmers. It was observed that nearly about 77% respondent realized change in climate and 23% respondent found no variation in climate; among them 69.5% respondent claimed temperature is increasing. About 55.1% respondent believed man made activity responsible for extreme event (i.e. flood, cyclone, drought etc) while 38.5% respondent believed nature is the responsible for extreme event. Most of the respondent (94.7%) found organic farming improves soil health. Crop residues are important source of soil organic matter which captures soil carbon by the formation of humus. About 86.1% respondent had concept about crop residue. Majority of the farmer (53.2%) claimed that composting increase soil organic matter. Conservation agriculture like crop rotation, cropping pattern, conservation, tillage and stubble retention irrigation and fertilization are the main drivers for SCS. Although most of the (57.2%) farmers had no idea about soil carbon and SCS but they followed various soils management practices for better crop yield (crop rotation 90.3%, irrigation 98.96% and fertilization 96.8%) which helps to increase soil organic carbon. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22124 J. Environ. Sci. & Natural Resources, 6(2): 233-238 2013